(untitled) (International Journal of Pharmaceutical and Life Sciences, 2012)
Present paper describes the interactions of Cephradine with different essential mineral salt like Magnesium Sulfate, Manganese Sulfate, Ferrous Sulfate, Zinc Sulfate and Potassium Chloride in an aqueous system at pH 7.4. This Magnesium Sulfate, Manganese Sulfate, Ferrous Sulfate, Zinc Sulfate and Potassium Chloride are essential trace element. From spectrophotometric study, it has been found that Cephradine forms 1:1 complex with Magnesium Sulfate, Manganese Sulfate, Ferrous Sulfate, Zinc Sulfate and Potassium Chloride. Spectral studies helps to detect the initial complexation between drug and mineral salts. Jobs plot at 7.4 provides same type of information. The Ardons spectrophotometric method confirmed the 1:1 complexation and the value of stability constants was calculated using Ardons plot. An individual antimicrobial study (MIC) of Cephradine in 1:1 mixture with Magnesium Sulfate, Manganese Sulfate, Ferrous Sulfate, Zinc Sulfate and Potassium Chloride at pH 7.4 was performed. These studies were carried out by observing the minimum inhibitory concentration (MIC) of the complexes and compared with the parent Cephradine against both Gram negative and Gram positive microorganisms in nutrient broth medium. Study confirms interactions of the Cephradine with Magnesium Sulfate, Manganese Sulfate, Ferrous Sulfate, Zinc Sulfate and Potassium Chloride and the interactions results into change the antimicrobial activity of Cephradine. Result shows that the antimicrobial activity increasing trends in presence of Magnesium Sulfate, Manganese Sulfate, Ferrous Sulfate and decreasing trends in presence of Zinc Sulfate and Potassium Chloride. DOI: http://dx.doi.org/10.3329/ijpls.v1i2.12953 International Journal of Pharmaceutical and Life Sciences Vol.1(2) 2012